Development of Augmented Reality Learning Media Based on Problem-Based Learning in Economics Subjects in High School - Dianita Br Silaban; R. Mursid; Samsidar Tanjung (FINGER : Jurnal Ilmiah Teknologi Pendidikan, 2026)
Background: The integration of innovative digital learning media is essential to help students understand abstract concepts in economics. Augmented Reality combined with Problem-Based Learning offers an interactive learning environment that supports conceptual understanding.Aim: This study aimed to develop an Augmented Reality learning medium based on PBL and evaluate its feasibility, practicality, and effectiveness in improving senior high school students’ economics learning outcomes.Methods: This Research and Development study employed the ADDIE model. The participants were 70 tenth-grade students assigned to an experimental class and a control class. Data were collected through expert validation, teacher and student response questionnaires, and learning outcome tests. Descriptive and inferential statistics were used for data analysis.Results: The developed media were highly feasible based on evaluations from subject matter experts (4.45), media experts (4.38), and instructional design experts (4.41). It was also highly practical according to teachers’ (4.47) and students’ (4.32) responses. A significant difference was found between the experimental and control groups (p < 0.05), with the experimental group achieving a higher mean posttest score (78.88) than the control group (71.17).Conclusion: The Problem Based Learning based Augmented Reality learning medium is feasible, practical, and effective for improving senior high school students’ economics learning outcomes.